(untitled) (Homoeopathy for All, 2025)
Tonsillitis is a common inflammatory condition of the palatine tonsils, primarily affecting children and adolescents. It is predominantly triggered by viral or bacterial acute throat infections (ATIs) and typically presents with sore throat, fever, and tonsillar hypertrophy. Although diagnosis is mostly clinical, differentiating between viral and bacterial causes can often be challenging. Recurrent tonsillitis is defined as the repeated occurrence of ATIs, interspersed with asymptomatic intervals or periods with minimal symptoms. This condition has far-reaching implications, including frequent school or work absenteeism, sleep disturbances, generalized discomfort, and increased healthcare visits all of which contribute to substantial socio-economic burden and diminished quality of life for patients and their families.